PERAN ORANGTUA DALAM PENDIDIKAN ANAK USIA SEKOLAH DASAR PADA KELUARGA PETANI DI DESA PARDOMUAN NAULI KECAMATAN PALIPI - Simbolon, Rinci; Sembiring, Supanri Jeremia; Tarigan, Selvia Theresia Br (JURNAL CURERE, 2023)
he purpose of this research was to identify the parents rale in educating elementary school-age children in farming families in Pardomuan Nauli Village, Palipi District, Samosir Regency. The approach used in this study was a qualitative approach with a population of all parents in the village with children of primary school age. The results of the study showed that parents had a very important role to play in encouraging and guiding the learning process in children. The role of parents in forming the character of children was very large. The role of parents includes role models, mentors, and motivators in children's education. Furthermore , this research also revealed the good role of parents in educating children in the aspects of faith, morals, intellectual, physical and social in the village. In conclusion, the researcher suggests that parents in Pardomuan Nauli Village increase their role in the education of elementary school-age children by giving sufficient attention, adequate encouragement, being a good role model, helping children have good learning discipline, and increasing supervision of children. in study. In addition, support from the government and the local community is also expected to improve the quality of education in the village.